The Impact of Financial Distress Risk to Malaysian Stock Return - Muhammad Noor Darwis, Nordin (2011)
If financial distress risk can be accurately predicted, the stock price of high distress risk companies should be discounted so as to enable investors to earn higher expected returns. Investors which have invested in high risk companies should be rewarded with high returns as the compensation in baring the risk due to the theory of risk and return trade off. This study set out a direct approach to examining the risk-return relationship of Malaysian companies. By applying Z-Score bankruptcy prediction model as the proxy of distress risk and the realized stock returns of the companies, this study found that the distress risk is not statistically significant enough to explain the expected stock returns. This result is contradicted with past research such as Shumway (1996) and Griffin and Lemmon (2002) which is firm with distress risk earn higher positive returns. However the size and book to market equity have shown significant relationship in explaining the stock returns of the companies. The theoretical expectations of the size and book to market equity effect on stock returns are supported in the Malaysian companies. These results are consistent with by Chan and Chen (1991), Fama and French (1992, 1995), Dichev (1998), Chen and Zhang (1998) and Griffin and Lemmon (2002) which found that size and book to market equity can be used in explaining stock returns.